A study of quantitative content of quercetin in the leaves of the schisandra chinensis - E. H. Galiakhmetova; N. V. Kudashkina; S. R. Khasanova (Сеченовский вестник, 2018)
The article deals with the issues of determining the content of the dominant flavonoid in alcohol extracts from the leaves of Schisandra chinensis, which are not an official type of raw materials. The chromatodensitometric method (high-performance thin-layer chromatography) was used in the studies, which allows not only to detect adsorption zones on the sorbent layer, but also gives a quantitative assessment of the resulting separation directly on the chromatographic plate. Pre-selected chromatography conditions (solvent system ethyl acetate-methanol-water (77 : 15 : 8), chromatographic plate «Sorbfil PTSH-P-А-UV», a method of extraction of the studied raw materials, extractant) at 365 nm allowed to develop a method of quantitative determination of quercetin in the leaves of Schisandra chinensis, a species introduced in the Republic of Bashkortostan. The optimal ratio of raw material and extractant (1 : 5) and the volume of samples of quantitatively applied extraction (0.025 ml) were determined by the height and area of the obtained peaks of adsorption zones on densitograms. As a result, we observed a linear relationship between the peak area and the quantitative content of quercetin in raw materials. The content of quercetin in the leaves of Schisandra chinensis vine amounted to 0,188 ± 0,004 %. Metrological analysis of the results showed the reproducibility of the technique and the absence of systematic error. Consequently, chromatodensitometric method can be used not only for semi-quantitative, but also for quantitative evaluation of the content of various substances in medicinal plant raw materials.